1996
DOI: 10.1016/0921-4534(96)00353-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Van Hove singularity on the electronic specific heat of high-Tc superconductors

Abstract: We study the influence of a logarithmic Van Hove singularity on the electronic specific heat C e of a 2D superconductor. The theoretical results are obtained for an isotropic s-wave gap parameter or an anisotropic dx2 y2-wave gap parameter. The specific heat jump at T c observed in high-T c superconductors can be reproduced by considering both gap parameter symmetries. However the very low temperature behavior of Ce as observed in a single crystal of YBa2Cu307_ ~ is only consistent with a gap parameter of dx2_… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…An experimental check of Refs. [1] or [2] is proposed here. The study of the influence of the doping rate and the effects of a magnetic field is more interesting work in our opinion than to use the best band structure with two transfer integrals, as opposed to employing phenomenological parameters as we did.…”
Section: (5)mentioning
confidence: 99%
See 2 more Smart Citations
“…An experimental check of Refs. [1] or [2] is proposed here. The study of the influence of the doping rate and the effects of a magnetic field is more interesting work in our opinion than to use the best band structure with two transfer integrals, as opposed to employing phenomenological parameters as we did.…”
Section: (5)mentioning
confidence: 99%
“…It will be an interesting check of the Bok and Bouvier comment [1] with respect to our work [2] whether the exponent is equal to 2 or 5/3. Finally, we agree that the real electronic band structure is indeed quite complicated.…”
Section: (5)mentioning
confidence: 99%
See 1 more Smart Citation
“…24. On the other hand, in a previous work, 25 we have studied the influence of a logarithmic VHS in the electronic density of states on the mean-field electronic specific heat C e,m f of a strictly two-dimensional ͑2D͒ superconductor. We have shown that experimental data on a YBa 2 Cu 3 O 7Ϫx single crystal 26 were in good agreement with an energy spectrum containing VHS and a d-wave gap parameter, especially in the low-temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a van Hove singularity vHs in the density of states DOS near or at the Fermi surface makes the standard BCS model more suitable for the high-T c cuprates 6,7,8 . The singularity in the density o f states known as the van Hove singularity arises wherever the group velocity v anishes and where there is a locally at region of the frequency as a function of the wavevector k. The critical points where these singularities are observed may be saddle points.…”
mentioning
confidence: 99%